2014
DOI: 10.1007/s00464-014-3811-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of warm-up on surgical performance: a systematic review

Abstract: Warming-up before an operative procedure improve a trainee's technical, cognitive, and psychomotor performance. Further studies are necessary to assess the ways in which warm-up could impact a surgeon's performance, and to identify the optimal timing and duration of warm-up prior to operating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…More recently, researchers have been investigating whether these simulators might yield shorter-term gains for trainees and experts alike, through the implementation of preoperative Òwarm-upsÓ [12,13]. The idea of warming up for surgery has largely been borrowed from sports medicine: there is a long history of elite athletes performing warm-up routines.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers have been investigating whether these simulators might yield shorter-term gains for trainees and experts alike, through the implementation of preoperative Òwarm-upsÓ [12,13]. The idea of warming up for surgery has largely been borrowed from sports medicine: there is a long history of elite athletes performing warm-up routines.…”
Section: Introductionmentioning
confidence: 99%
“…In the surgical field, the concept of warming up has been investigated primarily before conducting laparoscopic procedures [6][7][8][9]. A recent systematic review analyzed six prospective randomized trails that compared the effect of warming up by using surgical simulators before laparoscopic procedures, with control groups who had no warm-up [10]. The study concluded that warming up enhanced the surgeon's technical, cognitive and psychomotor performance.…”
Section: Introductionmentioning
confidence: 99%
“…However it's value was demonstrated in different studies [17,18]. In our opinion, TAPP is useful as "warm-up" procedure before to start other more complex techniques (e.g.…”
Section: )mentioning
confidence: 90%